Analysis of the Impact of Changes in Directors, IT Directors, and Risk Management of BSI (BRIS) on Information Technology Performance and Security and Risk Control at one of the BSI Bank Branches in Bandung City - Irwan Moridu; Erwina Kartika Devi; Pini Susanti; Siti Fatimah (West Science Business and Management, 2023)
This research studies the complex dynamics of leadership transitions in the banking sector, specifically focusing on the impact of changes in executive leadership positions - Director, IT Director, and Risk Management personnel - on Information Technology (IT) performance, IT security, and risk control at BSI Bank branches located in Bandung City. In today's rapidly evolving financial landscape, characterized by technological innovation and cybersecurity challenges, understanding how leadership changes affect these important aspects is critical. This research utilizes a mixed methods approach, combining surveys, interviews, and document analysis, to comprehensively explore the topic. The findings of this research reveal that leadership transitions exert a marked influence on IT performance, IT security, and risk control, underscoring the need for proactive strategies and effective alignment between leadership and IT and risk management teams. This research offers insights that are not only valuable to BSI Bank, but also pertinent to similar financial institutions navigating leadership changes while maintaining high standards in IT operations, security, and risk management.